Atopic dermatitis in childhood and adolescence - Werfel, Thomas 1959-; Spergel, Jonathan M.; Kiess, Wieland 1958- (Pediatric and adolescent medicine, 2011)
Atopic dermatitis is amongst the most common disorders of the skin in young people around the world. This timely book presents the newest insights and novel concepts in relation to all aspects of this skin disorder. Classification, clinical features and differential diagnosis are reviewed in the first chapter, while risk factors, susceptibility and an epidemiological overview are outlined in the next chapter, followed by a detailed discussion of the immunology of the skin and the pathophysiology of dermatitis. Further chapters present exciting new data delineating clinical aspects of current genetic findings and insights into concepts of neuroimmunology, as well as the very crucial and severe clinical aspect of itching. New data on the topic of inhalant allergy, specific immunologic treatments and the latest on food allergy are also included. A valuable reference for anyone interested in atopic dermatitis, this book is particularly useful for pediatricians and clinical practitioners seeing children and adolescents with atopic dermatitis on a daily basis